Inter-comparison of quantitative imaging of lutetium-177 (177Lu) in European hospitals - Wevrett, Jill; Fenwick, Andrew; Scuffham, James; Johansson, Lena; Gear, Jonathan; Schlögl, Susanne; Segbers, Marcel; Sjögreen-Gleisner, Katarina; Solný, Pavel; Lassmann, Michael; Tipping, Jill; Nisbet, Andrew (EJNMMI physics, 2018)
BACKGROUND: This inter-comparison exercise was performed to demonstrate the variability of quantitative SPECT/CT imaging for lutetium-177 (177Lu) in current clinical practice. Our aim was to assess the feasibility of using international inter-comparison exercises as a means to ensure consistency between clinical sites whilst enabling the sites to use their own choice of quantitative imaging protocols, specific to their systems. Dual-compartment concentric spherical sources of accurately known activity concentrations were prepared and sent to seven European clinical sites. The site staff were not aware of the true volumes or activity within the sources-they performed SPECT/CT imaging of the source, positioned within a water-filled phantom, using their own choice of parameters and reported their estimate of the activities within the source. RESULTS: The volumes reported by the participants for the inner section of the source were all within 29% of the true value and within 60% of the true value for the outer section. The activities reported by the participants for the inner section of the source were all within 20% of the true value, whilst those reported for the outer section were up to 83% different to the true value. CONCLUSIONS: A variety of calibration and segmentation methods were used by the participants for this exercise which demonstrated the variability of quantitative imaging across clinical sites. This paper presents a method to assess consistency between sites using different calibration and segmentation methods.
Keywords: Lutetium; Lu-177; SPECT/CT; Quantitative imaging; Molecular radiotherapy; PRRT